Ships That Sail No More : Marine Transportation from San Diego to Puget Sound 1910-1940 - Brown, Giles T. (Book collections on Project MUSE., 1966)
This chronicle of coastal shipping in the western United States forms an important but hitherto neglected part of the history of transportation in America. From the beginning the seaways were a vital link among the developing West Coast settlements, and even after the completion of a north-south rail line sturdy steamers continued to serve as the major carriers of freight and passengers along the Pacific Coast and as the chief economic and cultural contact of this region with the rest of America. Here, Giles T. Brown surveys this transportation system at the height of its activity and in parti.